1988
DOI: 10.1007/bf00436246
|View full text |Cite
|
Sign up to set email alerts
|

A study of dermatophytoses in Bangkok (Thailand)

Abstract: A total of 719 cases of dermatophytoses was studied in the Division of Dermatology, Department of Medicine, Siriraj Hospital, Mahidol University, Bangkok, Thailand, during January to December 1986. Infection caused by fungus comprises 12%, while the incidence of dermatophytoses was 5.5% of skin disorders. The age group commonly infected was 12-21 years old (mean age of 18 years); 40% was female and 47.5% was male. In the female patients the common prevalent infections were tinea corporis 29%, tinea cruris 23%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
2
3
0
1
Order By: Relevance
“…It was obvious that the age group from 11 to 20 years was more susceptible to tinea infections, 57 (31.1%) of all cases being recorded in this age group. Our results agree with those of Imwidthaya and Thianprasit [8] who found that dermatophytoses were prevalent in the 12–21‐year age group. Different dermatophytic diseases show some correlation with age of patients [4, 6].…”
Section: Resultssupporting
confidence: 93%
“…It was obvious that the age group from 11 to 20 years was more susceptible to tinea infections, 57 (31.1%) of all cases being recorded in this age group. Our results agree with those of Imwidthaya and Thianprasit [8] who found that dermatophytoses were prevalent in the 12–21‐year age group. Different dermatophytic diseases show some correlation with age of patients [4, 6].…”
Section: Resultssupporting
confidence: 93%
“…Mixed infections with two agents were also S. MARAKI g, Y. TSELENTIS than in female patients, as reported in other studies [6,7,181. The sex differences in the level of different tineae may be explained by different exposure to the causative fungi.…”
supporting
confidence: 78%
“…mentagrophytes or Tr. rubrum are the dominant species[4,6,[9][10][11][12][13][14][15][16][17]. All of these tineae can be attributed to the poverty of life and to poor hygienic conditions, particularly in the rural areas.…”
mentioning
confidence: 99%